Exploring housing policies in five Swedish municipalities: alternatives and priorities - Christina Heller; Lisa Ekstam; Maria Haak; Steven M. Schmidt; Björn Slaug (BMC, 2022)
Abstract Introduction Housing shortage due to population growth within metropolitan areas, combined with an ageing population, has put pressure on current housing provision in Sweden. Thus, there is an urgent need to develop sustainable housing policies to accommodate the growing number of seniors in accessible home environments. This study aimed to gain an in-depth understanding of how municipalities currently address housing accessibility issues and to explore what types of policy solutions they consider for the future. Material and methods Five Swedish municipalities were selected to represent a diversity of the population, housing provision approaches, and geographical areas. To understand current housing policies, two key actors (e.g. public officials, housing adaptation grant managers, city architects, etc.) from each municipality participated in semi-structured interviews (N = 10). Subsequently, those key actors, two senior citizens, and three researchers participated in a research circle to explore future policy solutions. Data were analyzed using content analysis. Results The interviews revealed common approaches to deal with housing accessibility issues such as regular renovations and maintenance, individual adaptations based on specific needs, and seeking collaboration with private housing actors on housing provision matters. Possible measures suggested for the future included increasing the national coordination of housing accessibility policies, amending legislation to only allow the construction of housing according to strengthened accessibility standards, and introducing economic incentives for seniors to move from housing with poor accessibility to more accessible accommodations. Conclusions Municipalities struggle with the lack of accessible and affordable housing for their ageing population, despite a large variety of policies from economic incentives to research and development policies. The results suggest that collaboration needs to be improved between all actors involved in housing policies. Preventive measures within the current laws may be needed to strengthen the construction of more accessible and affordable housing for populations ageing in place.